Spectra and waveforms of ELF transients in the Earth‐ionosphere cavity with small losses. Issue 2 (12th February 2014) - Nickolaenko, A. P.; Hayakawa, M.
Abstract Spectra and the waveforms are computed of the pulsed radio signals arriving from different distances to an observer in the Earth‐ionosphere cavity with the single‐scale exponential profile of air conductivity. The data were obtained for the cavity with exceptionally small losses. Spectra are compared of the signals in the realistic and an idealistic Earth‐ionosphere cavities. The waveforms are computed for such cavities and the pulse propagation velocities are evaluated. Studies of the Schumann resonance started from the ideal cavity model. Subsequent works dealt with the realistic propagation parameters and the ionosphere models on the Earth and other planets. However, the case of small losses is missing in the literature. We model ELF radio signals in such a cavity and demonstrate their noticeable distinctions from the customary records. In particular, the sinusoidal signals do not appear in the cavity with small losses, and instead, we obtain the sharp and large pulses. Computations show that the waveform propagating in the spherical cavity expands in time and reduces in amplitude. The time domain pulsed amplitudes were found at the source antipode and at the source point for the round‐the‐world wave. The latter becomes rather small even in the cavity with minor losses, so that autotriggering is unrealistic of a consecutive lightning discharge by the round‐the‐world echo even in a cavity with minor losses.